2010
DOI: 10.1016/j.ejso.2010.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum tumor marker determination on the management of women with borderline ovarian tumors: Multivariate analysis of a French multicentre study

Abstract: To cite this version:C. Poncelet, R. Fauvet, C. Yazbeck, C. Coutant, E. Darai. Impact of serum tumor marker determination on the management of women with borderline ovarian tumors: Multivariate analysis of a french multicentre study. EJSO -European Journal of Surgical Oncology, WB Saunders, 2010, 36 (11) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyeditin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
(29 reference statements)
2
8
0
Order By: Relevance
“…21 and Poncelet et al. 23 also support our findings that the CA19-9 level significantly increased especially in mMOTs. Our univariate analysis showed that mBOT diagnosed by FS in patients with a CEA level above the cut-off value may be associated with an increased risk of underdiagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…21 and Poncelet et al. 23 also support our findings that the CA19-9 level significantly increased especially in mMOTs. Our univariate analysis showed that mBOT diagnosed by FS in patients with a CEA level above the cut-off value may be associated with an increased risk of underdiagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, women who had these assays were more likely to have radical treatment (p \ 0.0001), intraoperative histology (p \ 0.0001) and a complete staging (p \ 0.004) [72]. Elevated CA-125 is found in up to 61% of women with BOT, although this marker may have value in identifying suspected BOT; clinicians should be aware that the levels might overlap between women with BOT and those with stage I invasive ovarian cancers [7].…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted in Singapore, Wong et al [21] have reported that the mean women's age at ovarian borderline tumors diagnosis was 38 years old, ranging from 16-89 years old. Another study developed in France have documented that one third of ovarian borderline tumors are diagnosed in women younger than 40 years old, and more than 80% of cases are detected early in an disease course [22]. Moreover, these tumors tend to affect women at a younger age than the typical EOCs in the USA [1].…”
Section: Discussionmentioning
confidence: 99%